Civil Revolution: User Experiences with British Columbia’s Online Court - Sykes, Katie; Dickson, Rebecca; Ewart, Sarah; Foulkes, Candice; Landry, Marina (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2020)
British Columbia’s new Civil Resolution Tribunal [CRT] is a primarily online dispute resolution system that has attracted international attention for its innovative approach.  But so far there has been little independent research on the effectiveness of the CRT and similar online dispute resolution initiatives in providing access to justice.  In a qualitative and exploratory study, we surveyed 49 British Columbians who had used the CRT about their experience with the process.  Overall, the results suggest that the CRT has improved access to justice, but the survey answers also identified problems and concerns, for which we suggest potential solutions.